Empowerment of Self Help Group Members of Virudhunagar District Through Vocational Trainings on Mushroom Production - S Muthuramu, V K Paulpandi, S Sakthivel, K Ramakrishnan and R Karthik (Journal of Krishi Vigyan, 2015)
Mushroom production can play a significant role to eradicate malnutrition, alleviate poverty and create employment opportunity for unemployed farm women in rural area. Vocational Training programme is generally conducted by the Krishi Vigyan Kendras with a goal that the trainee becomes an entrepreneur based on the acquired knowledge and skill. The vocational training programmes were conducted by Krishi Vigyan Kendra, Virudhunagar district to empower income generating ability of Self Help Groups (SHGs). Out of twelve SHGs trained, twenty five women from eight different SHGs were randomly selected for the present study. Findings of the study revealed that most of the trainees were in the age group of 21-35 yrs of age. Majority of them (36 %) were having education up to middle followed by matriculation (28 %). Four respondents (16 %) were landless, more than half (64 %) of these mushroom producers were small and marginal farm women and five (20%) were medium farm women. Total cost for mushroom production per unit was Rs. 44,823/- and gross income was Rs. 1,35,000/-. Hence each respondent may get Rs. 90,000/- as net income from their own unit every year. The mode of marketing was mainly direct sale in the unit itself, door delivery and local sale etc